Using the profiled elements to increase electrocyclone effectiveness - Anton Trinkunas; Lidia Pomortseva; Anatolii Titov; Zalina Rusinova (Chimica Techno Acta)
The article is devoted to flue gas cleaning, using fly ash as an example. Electrocyclone can be employed as gas-cleaning equipment. The electrocyclone operation can be intensified by reducing re-entrainment. The laboratory model of the annular channel of the electrocyclone is used to show the possibility of reducing re-entrainment by using the shaped elements of various designs on the collecting electrodes. Aerosol industrial emissions can be reduced by using an electrocyclone with modified collecting electrodes.